Examining the effects of anticipated policy actions: Results with the Finnish MICRO-QMED model - Pekka Sulamaa; Matti Virén (Bank of Finland, 1989)
This paper reports 'some policy simulations which have been carried out with the Finnish MICRO-QMED model. This rational expectations model built at the Economics Department of Bank of Finland is used to evaluate the short-run effects some anticipated policy actions. The paper also contains a short description of the MICRO-QMED model as well as a short user's guide for the model and for the MIKRO-TEKO programme used in simulating the model.
URN:NBN:fi:bof-201807301783
Keywords: 330